2020
DOI: 10.1037/edu0000442
|View full text |Cite
|
Sign up to set email alerts
|

Does perceived cohesion mediate the student personality–engagement relationship in the university setting?

Abstract: Student engagement has been established as a robust predictor of several positive outcomes related to academic development and success. Increasing our knowledge on what variables affect engagement can assist lecturers and other educational agents in maximizing student engagement within the university setting. The purpose of this study was to investigate the relationship between personality and student engagement via the mediational role of perceived cohesion in the university classroom. The model was tested us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…First, the closely related personality traits of neuroticism (from the five-factor model) and emotionality [54] have been linked with greater fear of crime in online samples [55], samples of students and neighborhood residents [56], and samples of long-time neighborhood residents [57]. Second, both extraversion and agreeableness have been linked to perceptions of social cohesion among students [58], on team tasks [59], and in families [60].…”
Section: The Indirect Roles Of Personalitymentioning
confidence: 99%
“…First, the closely related personality traits of neuroticism (from the five-factor model) and emotionality [54] have been linked with greater fear of crime in online samples [55], samples of students and neighborhood residents [56], and samples of long-time neighborhood residents [57]. Second, both extraversion and agreeableness have been linked to perceptions of social cohesion among students [58], on team tasks [59], and in families [60].…”
Section: The Indirect Roles Of Personalitymentioning
confidence: 99%
“…We expected, therefore, that higher levels of agreeableness are positively related to host-cultural engagement with natives and the performance of host-oriented behavior in general. Those students who are high on the conscientiousness factor are good planners and organizers and have excellent self-control and a strong commitment to their objectives and goals, showing higher school engagement (Bosselut et al, 2020; Heaven et al, 2007). Conscientiousness also has a role in behavioral control (Conner & Abraham, 2016).…”
Section: The Role Of Personality In the Process Of Acculturation And ...mentioning
confidence: 99%
“…Wildermuth et al (2013) found that several psychological-individual factors (e.g., meaningfulness) mediate the association between personality traits and engagement. Bosselut et al (2020) further suggested that individual factors would be a good candidate to examine this theoretical relationship after examining the mediating role of perception of team cohesion in the relationship between personality and engagement by using the context-input-process-outcome (CIPO) model. Our study, therefore, explores the mediating role of negotiable fate (a psychological factor) in the relationship between grit (personality trait) and engagement (academic outcome).…”
Section: Introductionmentioning
confidence: 99%